Integration of organic–inorganic nitrogen fertilization on nitrogen conversion in soil - Ahmad, Akhlaq; Khan, Aaqil; Ullah, Farhan; Hassan, Muhammad Ahmad; Iqbal, Javed; Jun, Wang; He, Song; Zhaorong, Dong (Frontiers in Plant Science, 2025)
The excessive use of inorganic nitrogen fertilizers poses significant environmental threats, including nitrate leaching and greenhouse gas emissions. Conversely, organic fertilizers enhance soil microbial activity and long-term fertility. This study investigates the integrated application of organic and inorganic nitrogen fertilizers to optimize soil health and crop productivity while mitigating environmental impacts. A field experiment was conducted over a single maize growing season using a randomized block design. Six treatments were applied: no fertilizer (T1), chemical fertilizer only (T2), 15% (T3), 30% (T4), or 45% (T5) sheep manure combined with chemical fertilizer, and sheep manure only (T6). Soil samples were analyzed for pH, dissolved organic carbon (DOC), nitrate (NO₃⁻), ammonium (NH₄⁺), and the microbial gene abundance of key nitrifiers (AOA, AOB) and denitrifiers (nirK, nirS). The 100% sheep manure treatment (T6) resulted in significantly higher soil DOC (34 ± 4.58 mg/kg) and NO₃⁻ (3.31 ± 0.51 mg/kg) concentrations, promoting enhanced microbial diversity and activity. In contrast, the inorganic-only treatment (T2) yielded the highest grain nitrogen content (9.43 ± 2.24 mg/kg), indicating immediate nutrient availability. Heat map and Principal Component Analysis (PCA) revealed distinct clustering of microbial gene expressions (AOA, AOB, nirK, nirS) in response to fertilization, with high organic inputs fostering a more diverse and active microbial community. Redundancy Analysis (RDA) showed strong correlations between these environmental factors and gene expression. The results demonstrate that integrating organic and inorganic fertilizers creates a synergistic effect. This approach optimizes nutrient cycling by balancing immediate crop availability with long-term soil building. It enhances microbial functional capacity for nitrification and denitrification, thereby improving soil health and reducing potential environmental impacts like nitrate leaching and greenhouse gas emissions. We conclude that the integration of organic and inorganic fertilization is a key strategy for supporting sustainable agricultural productivity.